Interview with the Canary Islands education inspector D. Jacinto R. Quevedo Sarmiento - Editorial, Equipo (Avances en Supervisión Educativa, 2018)
Jacinto R. Quevedo Sarmiento, professor of mathematics since 1979 and inspector of education since 1993, since two school years chairs the Evaluation Committee of the procedure of detection, supervision, recognition and dissemination of Good Teaching Practices that has been carried out in the Community Autonomous of the Canary Islands. A procedure where the inspection of education plays an essential role in recognizing those good teaching practices that are worthy of declaration of educational interest, distinguishing those teaching and learning experiences in which are present features such as the following: inclusive education, teamwork of students, use of ICT resources, competence methodology, evaluation of teaching practice, among others.From his professional experience, Avances interviews him not only to know the task that the educational inspection carries out in the procedure of detection of good practices, but also his personal opinion on the changes that in the educational inspection have taken place in the last years.Thank you for giving us your time.
Keywords: interview